Base-isolated structure equipped with tuned liquid column damper: An experimental study. (1st February 2019) - Furtmüller, Thomas; Di Matteo, Alberto; Adam, Christoph; Pirrotta, Antonina
Highlights: Experimental verification of control performance for hybrid controlled system. Identification of relevant dynamic nonlinear base-isolation and TLCD parameters. Derivation of analytical model verifying experimental results. Abstract: In this study, a novel passive vibration control strategy is investigated experimentally, where a Tuned Liquid Column Damper protects a base-isolated structure. The Tuned Liquid Column Damper is attached to the base, in contrast to typical attachment points of passive energy dissipation devices in high-rise buildings at elevated levels. Experiments on a base-excited small-scale three-story shear frame are conducted in order to study effects of both control devices – base-isolation and Tuned Liquid Column Damper – on the structural model. The dynamic properties of the stand-alone shear frame and the base-isolation subsystem are derived using standard dynamic test methods based on displacement and acceleration response measurements. In the base-isolation subsystem both viscous damping and friction effects are identified. The water level of the Tuned Liquid Column Damper is tracked by means of computational image processing of video recordings, facilitating the identification of the fundamental liquid motion mode as well as the nonlinear damping properties. An experimental parametric study is conducted for three Tuned Liquid Column Damper devices with different frequency tuning ratios. The assessment of the hybrid control strategy is based on the determined transfer functions of the studied setups. Experimental outcomes confirm recent theoretical findings that a passive hybrid control strategy combining a base-isolation and a Tuned Liquid Column Damper reduces the displacement demand of the base-isolation subsystem as well as the total story acceleration demand if both control devices are properly tuned.